The Quality of Gaga Roosters Semen During Cold Storage Using a Diluent Supplemented with Sorbitol - Khaeruddin; Ciptadi, G.; Yusuf, M.; Fattah, A. H.; Junaedi; Syamsuryadi, B.; Wahjuningsih, S. (Tropical Animal Science Journal, 2024)
This study aimed to examine the effect of adding different concentrations of sorbitol to the Ringer’s lactate-egg yolk (RLEY) diluent on the quality of Gaga roosters’ semen during cold storage. A completely randomized design was used with 10 replicates and 4 levels of diluent treatment, including control, 1%, 2%, and 3% sorbitol. Semen was collected using a massage method, followed by fresh semen evaluation and dilution with a ratio of 1:5. Semen was stored at a cold temperature (5 ºC) and observed after 0, 24, 48, and 72 hours. The variables observed were semen pH, motility, kinematics, viability, plasma membrane integrity, acrosome integrity, malondialdehyde (MDA), and intracellular calcium ion (Ca2+) concentrations of sperm. All data were analyzed using analysis of variance (ANOVA). Subsequently, the evaluation of sperm mitochondrial activity and DNA damage was carried out, and the data were analyzed using the T-test. The results showed that treatment with sorbitol in the diluent had no effect on semen pH, kinematics (except straightness), acrosomal cap integrity, DNA damage, mitochondrial activity, and MDA concentration. However, sorbitol concentrations significantly affect (p<0.05) total motility, progressive motility, static motility, STR, viability, plasma membrane integrity, and intracellular Ca2+. In conclusion, the addition of 1-3% sorbitol preserves the quality of Gaga roosters’ semen during 72 hours of cold storage.